Outcome of primary peritoneal drainage in perforated necrotizing enterocolitis: an experience with 96 infants - Rashid, Kumar Abdul; Wani, Reyaz Ahmad; Tak, Shafat Ahmad; Masood, Omar; Samie, Amat U.; Magray, Mudasir Ahmad; Jan, Muzaffar Ahmad (International Surgery Journal, 2021)
Background: Necrotizing enterocolitis is a life-threatening inflammation of neonatal intestine of multifactorial etiology. In early stages, medical management is considered; while as a transmural disease with pneumatosis or perforation needs surgical attention. Primary peritoneal drainage has evolved as an alternative to classic exploratory laparotomy especially in sick preterm and very low birth weight infants. Methods: In our study, we tried to employ primary peritoneal drainage as an initial intervention in all surgical necrotizing enterocolitis patients and analyzed the results and final outcome in terms of total days in neonatal intensive care unit, total parenteral nutrition days, days to start oral feeds, need for laparotomy, mortality and other complications. Results: Around one-third patients were either very low or extremely low birth weight and 80% patients were preterm. Primary peritoneal drainage was successful without need for laparotomy in around 65% of patients. In the rest 34 patients, 24 were subjected to rescue laparotomy, while 10 could not be stabilized for major surgery. Overall mortality was 29.16%. Conclusions: Early bedside primary peritoneal drainage can be employed in all cases of NEC with perforation with rescue laparotomy to be determined by subsequent monitoring. This strategy seems to be safe and cost-effective in a resource challenged set up and lifesaving in sick and extremely low birth weight infants.